Equipment for processing sugar - (:unkn) unknown (My University, 2013)
Mill turbine and gearbox used to grind sugar cane at the mill house.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar machinery -- Trinidad and Tobago